The relationship between financial literacy and financial fragility: the moderation effects of psychological, economic and social factors - Damanyi Gideon (KNUST, 2024)
A thesis submitted to the department of accounting and finance, kwame nkrumah university of science and technology in partial fulfillment of the requirements for the degree of master of science in accounting and finance